Determinantes da taxa de câmbio real, teoria e evidencias empíricas: uma aplicação para o Brasil - Ailton Braga (Economia Aplicada, 2024)
We test for the Brazilian economy three theories for the determination of the real exchange rate: 1. The theory of the Purchase Power Parity (PPP) relative, which implies constant real exchange rate; 2. The hypothesis of the relative variation of the productivity, which asserts that the increase of the productivity differential between producer sector of traded goods and the producer sector of no traded goods of a country regarding other countries carries to the real valorization ofthe exchange rate; 3. The transfers effect, which affirms that the income transfers abroad generate real devaluation of the exchange rate, and the transfers receipt generates valorization. The results carried to the rejection of PPP relative and to the confirmation of the importance of the relative variation of the productivity and of the transfers effect in the determination of the real exchange rate of Brazil. The rejection of PPP relative implies do not there be a constant balance rate, to the which the exchange rate always would return. And the importance of the relative variation ofthe productivity and ofthe transfers effect makes the rate ofreal exchange rate be subject the flotations certain for real variables, like the relative productivity abroad and the net external passive.